ANALISIS STRATEGI PENGEMBANGAN UKM RUBATH COFFEE JOMBANG JAWA TIMUR - Aminah Happy Moninthofa Ariyani; Ayu Candra Wulan; Andrie Kisroh Sunyigono; Slamet Subari (Journal of Integrated Agribusiness, 2022)
UKM Rubath Coffee is one of the SMEs in East Java that sells processed coffee as a beverage product and was established in 2017. The large number of SMEs with similar products makes it a fierce competition between entrepreneurs. In that case, SMEs are required to develop their businesses. The purpose of this study is to analyze internal and external factors and formulate alternative strategies in developing Rubath Coffee SMEs. The study was conducted using the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats). The factor that influences business development is in quadrant III (Turn Around) which is a position to change strategy. This position has a combination of weakness (W) and opportunity (O). It is expected to develop a business based on the quadrant of the position of SMEs to be located, so that SMEs immediately rise to overcome weaknesses while improving organizational performance by taking appropriate use of opportunities. The recommended strategies are Improving Business Management, Adding Distribution Channels in Potential Areas and Training and Developing Human Resources.